The WTO Agreement on Trade-Related Aspects of Intellectual Property Rights and the Doha Declaration on TRIPS and Public Health: Will They Solve the Pharmaceutical Question? - Lima, Rafael Cavazzoni (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Laws in International Law at the Fletcher School of Law and Diplomacy. Abstract: The Agreement in Trade-Related Intellectual Property Rights (the TRIPs Agreement) transformed the standing of intellectual property in international law by incorporating into the legal framework of the World Trade Organization (WTO) an improved system of standards for the protection of a full range of intellectual property (IP) rights, including copyrights, patents, trademarks, industrial designs, trade secrets and geographical indications. This paper intends to offer the reader an analysis of the impact of the TRIPs agreement on the access to medicines in developing countries. More specifically, this dissertation aims to elucidate and explain the existing legal regime regulating the grant of compulsory licenses by developing countries for the implementation of domestic programs in the area of public health after the Doha Declaration. This legal examination will be followed by an interesting policy-oriented analysis. In this part of the paper, the cases of Rwanda, Brazil and Thailand will be properly addressed. The intention is to provide an opinion about the system that is currently in place and to analyze whether the Doha Declaration and sequential actions were able to put an end to what was referred to as "The Pharmaceutical Question." Finally, the paper will offer a few ideas for making this system work better.